The written and the visual - Łuczyńska-Hołdys, Małgorzata (V&R unipress, 2021)
The author investigates the points of contact between literature, visual arts and feminist criticism by offering fresh readings of selected Romantic and Victorian poems about women and a discussion of their wide-ranging visual history – a subject which has not yet been undertaken in a book-length study. The innovative feature of the project lies in its scope and merit: extensive readings of 19th century poetry, informed by carefully chosen critical approaches, are followed by a rich overview and analysis of visual renderings of the poems in question. Łuczyńska-Hołdys has succeeded in bringing to light previously unknown or undiscussed works, and reappraised many well-known paintings and illustrations. Angaben zur beteiligten Person Łuczyńska-Hołdys: Małgorzata Łuczyńska-Hołdys is an Associate Professor at the University of Warsaw, Poland. She specialises in Romantic and Victorian literature and culture. She has published widely on W. Blake, J. Keats, D. G. Rossetti and the Pre-Raphaelites.
10.14220/9783737012539
Keywords: English poetry; Women in literature; Women in art; book illustration; 19th century English poetry; Gender Studies; Pre-Raphaelites; Romantic poems; English Studies; Victorian poems; Visual history; Poésie anglaise - 19e siècle - Histoire et critique; Femmes dans la littérature; Femmes dans l'art; Criticism; interpretation; etc